Gross Anatomy of the Scapula of Pygmy Hog (Porcula salvania) - Deka, Anil; Baishya, Gajen; Das, Bidyut Jyoti; Talukdar, Manmath; Kalita, Pranab Ch. (Indian Journal of Veterinary Anatomy, 2013)
The present gross morphological study was conducted on the scapula of three adult pygmy hogs. The scapular spine was cranially placed and a foramen was present on the dorsal border of the scapula towards infraspinatous fossa. The neck of the scapula was long. The total length of scapula without cartilage was 11.5 cm. The width of scapula at medial surface from cranial angle to caudal angle was 5.4 cm while at the distal end it was 1.4 cm. The glenoid cavity was oval and deep. A less prominent supraglenoid tubercle was located on the rim of the glenoid cavity whereas, coracoid process was well developed. The subscapular fossa was more deep and extensive. The serrated muscular area on the medial surface was comprised of a triangular shaped area directed cranio-caudally.